The Effect of Tax Transparency on the Effectiveness of Indonesia’s Mining Tax Policy - Laksana, Andri Winjaya; Bambang Manumayoso; Arida Turymshayeva (Contrarius, 2026)
The mining sector is a crucial pillar of the Indonesian economy and contributes significantly to state revenues. However, the effectiveness of mining tax policies continues to face various challenges, particularly low tax transparency, weak oversight, and tax avoidance through transfer pricing schemes, profit shifting, and inaccurate reporting. This research examines the current state of mining tax policies in Indonesia, determines the role of tax transparency in enhancing the effectiveness of these policies, and identifies the transparency reforms necessary to minimise tax avoidance in the mining sector. This study employs a normative juridical research method, utilising statutory, comparative, and conceptual approaches. This study identifies three principal findings concerning the regulation and implementation of mining taxation in Indonesia. First, the Indonesian government has developed mining tax regulations to increase state revenue and strengthen oversight of mining activities. However, the existing regulatory framework still contains several structural weaknesses, particularly in the substance of legal norms, the effectiveness of supervisory institutions, and the institutional culture of transparency, which collectively create opportunities for tax avoidance practices. Second, the analysis demonstrates that tax transparency plays a crucial role in strengthening the effectiveness of mining tax governance. Comparative regulatory practices in several developed jurisdictions show that transparency mechanisms, including mandatory reporting obligations, standardized fiscal data systems, and public disclosure of financial information, significantly reduce opportunities for tax avoidance. Third, Indonesia can improve the effectiveness of its mining taxation regime by implementing transparency based regulatory reforms, including project level reporting, data standardization aligned with international initiatives, open data platforms, independent audits, and beneficial ownership disclosure to enhance accountability and sustainable natural resource governance.